Phellinus tropicalis Abscesses in a Patient with Chronic Granulomatous Disease - Ramesh, Manish; Resnick, Elena; Hui, Yiqun; Maglione, Paul J.; Mehta, Harshna; Kattan, Jacob; Bouvier, Nicole M.; LaBombardi, Vincent; Victor, Tanya R.; Chaturvedi, Sudha; Cunningham-Rundles, Charlotte (Journal of clinical immunology, 2014)
Chronic Granulomatous Disease (CGD), caused by genetic defects in components of the phagocyte NADPH oxidase pathway, leads to recurrent life-threatening bacterial and invasive fungal infections. While a number of unique pathogens have been associated with this disease, the causative organisms may be difficult to identify. Here, we present a 24 year old male with known X-linked CGD who concurrently developed a cervical abscess and an abscess in the subcutaneous tissues of the right hip, both of which were surgically drained. Cultures failed to identify any organisms. He was treated empirically with ertapenem but the hip abscess recurred at the original site and in contiguous dependent areas in the posterior thigh and knee. A filamentous organism was observed microscopically, initially considered a contaminant, but on culture yielded a mold growth, identified as Phellinus tropicalis (synonym: Inonotus tropicalis ) based on phenotypic and molecular methods. This is the third case report of human infection with P. tropicalis , all in subjects with CGD. The patient was treated with voriconazole with resolution of his symptoms.